Aliskiren and the calcium channel blocker amlodipine combination as an initial treatment strategy for hypertension control (ACCELERATE): a randomised, parallel-group trial - Brown, Morris J; McInnes, Gordon T; Papst, Cheraz Cherif; Zhang, Jack; MacDonald, Thomas M (The Lancet (British edition), 2011)
Short-term studies have suggested that the use of initial combination therapy for the control of blood pressure improves early effectiveness. We tested whether a combination of aliskiren and amlodipine is superior to each monotherapy in early control of blood pressure without excess of adverse events, and if initial control by monotherapy impairs subsequent control by combination therapy. We did a double-blind, randomised, parallel-group, superiority trial at 146 primary and secondary care sites in ten countries, with enrolment from Nov 28, 2008, to July 15, 2009. Patients eligible for enrolment had essential hypertension, were aged 18 years or older, and had systolic blood pressure between 150 and 180 mm Hg. Patients were randomly assigned (1:1:2) to treatment with 150 mg aliskiren plus placebo, 5 mg amlodipine plus placebo, or 150 mg aliskiren plus 5 mg amlodipine. Random assignment was through a central interactive voice response system and treatment allocation was masked from the patients. From 16–32 weeks, all patients received combination therapy with 300 mg aliskiren plus 10 mg amlodipine. Our primary endpoints, assessed on an intention-to-treat basis (ie, in patients who received the allocated treatment), were the adjusted mean reduction in systolic blood pressure from baseline over 8 to 24 weeks, and then the final reduction at 24 weeks. This trial is registered with ClinicalTrials.gov, number NCT00797862. 318 patients were randomly assigned to aliskiren, 316 to amlodipine, and 620 to aliskiren plus amlodipine. 315 patients initially allocated to aliskiren, 315 allocated to amlodipine, and 617 allocated to aliskiren plus amlodipine were available for analysis. Patients given initial combination therapy had a 6·5 mm Hg (95% CI 5·3 to 7·7) greater reduction in mean systolic blood pressure than the monotherapy groups (p<0·0001). At 24 weeks, when all patients were on combination treatment, the difference was 1·4 mm Hg (95% CI −0·05 to 2·9; p=0·059). Adverse events caused withdrawal of 85 patients (14%) from the initial aliskiren plus amlodipine group, 45 (14%) from the aliskiren group, and 58 (18%) from the amlodipine group. Adverse events were peripheral oedema, hypotension, or orthostatic hypotension. We believe that routine initial reduction in blood pressure (>150 mm Hg) with a combination such as aliskiren plus amlodipine can be recommended. Novartis Pharma AG.